2019
DOI: 10.1007/s00382-019-04973-0
|View full text |Cite
|
Sign up to set email alerts
|

The impact of air–sea coupling and ocean biases on the seasonal cycle of southern West African precipitation

Abstract: The biannual seasonal rainfall regime over the southern part of West Africa is characterised by two wet seasons, separated by the 'Little Dry Season' in July-August. Lower rainfall totals during this intervening dry season may be detrimental for crop yields over a region with a dense population that depends on agricultural output. Coupled Model Intercomparison Project Phase 5 (CMIP5) models do not correctly capture this seasonal regime, and instead generate a single wet season, peaking at the observed timing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 53 publications
(124 reference statements)
0
8
0
Order By: Relevance
“…The ERA5 dataset, a reanalysis product from the European Centre for Medium-Range Weather Forecasts (ECMWF, Hersbach et al, 2020), is used as a reference to evaluate the performance of the CMIP6 models in simulating the surface and atmospheric fields under present-day conditions. ERA5 has replaced ERA-Interim (Dee et al, 2011), which has been widely used to study the characteristics of the West African climate (Manzanas et al, 2014;Lavaysse et al, 2015;Kebe et al, 2016;Raj et al, 2018;Maranan et al, 2018;Diakhaté et al, 2019Diakhaté et al, , 2020Wainwright et al, 2019). ERA5, for instance, shows an improvement of the rainfall representation over Burkina Faso (Tall et al, 2019), which is a part of the Sahelian region.…”
Section: Reanalysis Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The ERA5 dataset, a reanalysis product from the European Centre for Medium-Range Weather Forecasts (ECMWF, Hersbach et al, 2020), is used as a reference to evaluate the performance of the CMIP6 models in simulating the surface and atmospheric fields under present-day conditions. ERA5 has replaced ERA-Interim (Dee et al, 2011), which has been widely used to study the characteristics of the West African climate (Manzanas et al, 2014;Lavaysse et al, 2015;Kebe et al, 2016;Raj et al, 2018;Maranan et al, 2018;Diakhaté et al, 2019Diakhaté et al, , 2020Wainwright et al, 2019). ERA5, for instance, shows an improvement of the rainfall representation over Burkina Faso (Tall et al, 2019), which is a part of the Sahelian region.…”
Section: Reanalysis Datamentioning
confidence: 99%
“…As a consequence, during July and August, the atmospheric circulation above the Guinea Coast is characterized by a downward flow at upper levels. This leads to the so-called "little dry season" (Adejuwon and Odekunle, 2006;Fink et al, 2017;Wainwright et al, 2019), during which the Guinea coast rainfall decreases in magnitude compared to its mean over the April-May-June season. Over the 20th century, the interannual variability of the Guinea Coast rainfall was strongly influenced by the sea surface temperature (SST) fluctuations in the eastern equatorial Atlantic (Giannini, 2003;Polo et al, 2008;Suárez-Moreno et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The CMIP5 models are also known to overestimate the rainfall in coastal areas of West Africa during the "little dry season" (Sow et al, 2020). Wainwright et al (2019) have demonstrated that the misrepresentation of the July-August Guinean Coast rainfall in these models comes from the positive SST biases in the Atlantic Ocean, which strengthen the rising motions over the Guinea Coast and increase the rainfall. Consistently, the CMIP6 ensemble mean exhibits a positive (negative) mean SST bias in the eastern (western) part of the tropical Atlantic, as depicted in Fig.…”
Section: Guinean Coast Rainfall: Annual Cycle Variability and Jas Meanmentioning
confidence: 94%
“…The ERA5 dataset, a reanalysis product from the European Centre for Medium-Range Weather Forecasts (ECMWF, Hersbach et al, 2020), is used as a reference to evaluate the performance of the CMIP6 models in simulating the surface and atmospheric fields under present-day conditions. ERA5 has replaced ERA-Interim (Dee et al, 2011) that has been widely used to study the characteristics of the West African climate (Manzanas et al, 2014;Lavaysse et al, 2015;Kebe et al, 2016;Raj et al, 2018;Maranan et al, 2018;Diakhaté et al, 2019Diakhaté et al, , 2020Wainwright et al, 2019). ERA5 for instance shows an improvement of the rainfall representation over Burkina Faso (Tall et al, 2019), which is a part of the Sahelian region.…”
Section: Methodsmentioning
confidence: 99%
“…The ERA5 dataset, a reanalysis product from the European Centre for Medium-Range Weather Forecasts (ECMWF, Hersbach et al, 2020), is used as a reference to evaluate the performance of the CMIP6 models in simulating the surface and atmospheric fields under present-day conditions. ERA5 has replaced ERA-Interim (Dee et al, 2011) that has been widely used to study the characteristics of the West African climate (Manzanas et al, 2014;Lavaysse et al, 2015;Kebe et al, 2016;Raj et al, 2018;Maranan et al, 2018;Diakhaté et al, 2019Diakhaté et al, , 2020Wainwright et al, 2019). ERA5 for instance shows an improvement of the rainfall representation over Burkina Faso (Tall et al, 2019), which is a part of the Sahelian region.…”
Section: Methodsmentioning
confidence: 99%